Incidence and predictors of 14-day mortality in multidrug-resistant Acinetobacter baumannii in ventilator-associated pneumonia - Almomani, Basima Abdalla; McCullough, Amanda; Gharaibeh, Rawan; Samrah, Shaher; Mahasneh, Fatimah (The Journal of Infection in Developing Countries, 2015)
Introduction: Ventilator-associated pneumonia (VAP) caused by multidrug-resistant Acinetobacter baumannii (MDR-AB) is common in hospitals and impacts patient survival. We determined the incidence of MDR-AB VAP in critical care units and examined the predictors of 14-day mortality in these patients. Methodology: A retrospective case series study was conducted at a tertiary referral teaching hospital in north Jordan. A list of patients with a positive culture of A. baumannii between January 2007 and June 2013 was retrieved using computerized hospital databases. Medical records of all these patients were reviewed, and cases of VAP infected with MDR-AB were identified. Predictors of 14-day mortality were determined using multivariable logistic regression adjusted for possible confounders. Results: Out of 121 A. baumannii-VAP cases, 119 (98.3%) were caused by MDR-AB. The incidence rate of MDR-AB VAP was 1.59 cases per 100 critical care unit admissions. The mortality of A. baumannii-VAP cases in critical care units was 42% (50/119). Being prescribed two or more definitive antibiotics (prescribed based on susceptibility data) (OR = 0.075, 95% CI = 0.017–0.340, p = 0.001) and ipratropium/salbutamol during mechanical ventilation (OR = 0.140, 95% CI = 0.028–0.705, p = 0.017) were independently associated with lower hospital mortality. Conclusions: Our results suggest incidence of MDR-AB VAP in critical care units is high and that prescription of antibiotics based on antibiotic susceptibility and use of bronchodilators is associated with lower mortality in this population. Larger prospective studies are needed to explore whether these findings can be replicated in different clinical settings.